O desenho de sequências de aprendizagem como estratégia para o desenvolvimento profissional docente no ensino médio técnico do Senac São Paulo - Zatti, José Pablo (2021)
This work aims to verify the impact of learning design sequences, as a training strategy, on teacher professional development though an analysis of a learning process of a group of Technical and Vocational Education and Training (TVET) teachers. To support the analysis, I mainly adopted Carlos Marcelo Garcia’s studies on teacher professional development and the formal and informal process of learning to teach, Lee S. Shulman’s study on the knowledge base of teaching and Donald A. Schön’s study on the reflective practice that is inherent to teaching. The research was conducted with a group of teachers of the São Miguel branch of Senac São Paulo. This group was set up when the TVET course in Information Technology, which is characterized by its integrated curriculum, was implemented at that school. Through an analysis of the statements collected from surveys and the examination of the reports produced during the continuing education process of those teachers, it was possible to observe several formal and informal learning experiences in different moments of their educational process, and their perception of the impact of those experiences on their teaching education and on their teaching practice. In that context, and based on the statements and data collected, the experience that was identified by learning design sequences is described and analyzed in relation to its effect on teacher professional development.